Tradisi Kukhuk Limau Ditinjau Dari Pendekatan Psikologis Dalam Studi Islam - Sugiyanti; Susi Novianti; Sutarmi; Syamsiatul Fadilah; Winda Prasetyani Utami; Muhammad Syaifullah (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
The aim of this research is to determine the meaning and value of the Kukhuk Limau tradition in terms of a psychological approach in Islamic studies. This research is research using library research which uses a descriptive qualitative approach. The results of the discussion of this paper are that pregnancy thanksgiving traditions such as Kukhuk Limau in Islam reflect various psychological aspects related to happiness, mental readiness, and social relationships in a religious context. In the psychological approach in Islamic studies, this tradition can be interpreted as: 1) Mental and Emotional Readiness, where this tradition provides an opportunity for prospective parents to celebrate and appreciate the gift of pregnancy with joy and gratitude. This can help strengthen the emotional bond between a married couple and prepare them mentally for the role of parents. 2) Social Relations and Community Support, where this tradition involves family, friends and the community as a form of social support and solidarity. In an Islamic psychology perspective, this social support is important for strengthening family ties and building a supportive social network, which can then help reduce stress and anxiety related to pregnancy, and 3) Spirituality and Gratitude, where pregnancy thanksgiving is also a moment to strengthen connections. spiritual relationship with Allah and express gratitude for the gift of pregnancy. In Islam, appreciation for Allah's blessings is an important part of worship, and the tradition of thanksgiving is one way to express this gratitude.